Posterior stromal ripples increase risk of Descemet's membrane endothelial keratoplasty graft detachment worsening over time. Issue 2 (19th September 2022) - Coco, Giulia; Levis, Hannah J.; Borgia, Alfredo; Romano, Davide; Pagano, Luca; Virgili, Gianni; Kaye, Stephen B.; Romano, Vito
Abstract: Purpose: To evaluate anterior segment optical coherence tomography (AS‐OCT) features of Descemet's membrane endothelial keratoplasty (DMEK) grafts associated with graft attachment worsening over time. Methods: Retrospective case series on patients who received uncomplicated DMEK surgery and for whom subsequent AS‐OCT data were available for analysis. Patients' demographics and surgical details were collected. AS‐OCT was analysed for graft detachment axial extension, presence of posterior stromal ripples, quadrant involvement (location and number), degree of detachment extension, peripheral roll, presence and amount of air in the anterior chamber (AC). Features associated with re‐bubbling and graft detachment worsening over time were identified. Results: A total of 147 patients with a mean age of 70.8 ± 9.8 years (63% females) were included. AS‐OCT was performed at 2.9 ± 2.4 days after surgery. AS‐OCT factors associated with re‐bubbling were posterior stromal ripples ( p = 0.004) and detachment axial extension ( p < 0.001). At first follow‐up, of the 147 DMEK, 67 showed complete attachment and 80 partial detachment. In those cases of initially completely attached grafts, posterior stromal ripples were associated with the risk of subsequent graft detachment ( p = 0.014) together with recipient age ( p = 0.043), phaco‐combined surgery ( p = 0.018) and AS‐OCT timing ( p = 0.033); while, in the initially partially detached grafts, detachment worsening was associated with posterior stromal ripples ( p = 0.025), detachment axial extension ( p = 0.003), degrees of detachment involvement ( p = 0.029), peripheral roll‐in shape ( p = 0.033) and presence of air in the AC ( p = 0.032). Relative risk (RR) of graft detachment worsening in patients with moderate/severe posterior stromal ripples was 1.75 (95% CI = 1.09–2.81). Conclusion: Posterior stromal ripples and detachment axial extension >1/3 of graft surface area were the main risk factors for detachment worsening over time, and patients showing these features should be monitored closely to identify the need for re‐bubbling at an early stage, thus improving surgical outcomes.